Central banking in undeveloped money markets - Sen, Satyendranath (Calcutta, Bookland Private, ltd., 1961)
A large part of the book has been devoted to an examination of the conditions prevailing in the countries included in the British Common Wealth of Nations, with some reference to the experience of a few Latin American countries.
Includes index
osc 25/4/17
Loans
Keywords: Banks and banking, Central; Central Banking; Money market